THE DESIGNING A RECIPE FOR YOGURT ENRICHED WITH HEMP FLOUR, JERUSALEM ARTICHOKE SYRUP AND AGAVE SYRUP - O. E. Krotova; A. S. Chernyshkov; K. E. Khalagaeva (Современная наука и инновации)
In this paper, the authors considered a matrix method for developing a formula for a fermented milk product with a high protein content, by enriching yogurt with vegetable components: hemp flour, 122erusalem artichoke syrup and agave syrup. Using the obtained recipes, samples of fermented milk products were prepared and tasting was carried out. According to the organoleptic results, the expediency of using the matrix method of computer modeling in the development of formulations of fermented milk products is confirmed. People with diabetes and those who lead a healthy lifestyle, because the protein content in the samples has been increased to 3.7% and the introduction of sugar is excluded can recommend the resulting yogurts for use. The development of formulations of fermented milk products with a high protein content, carried out by the matrix method, made it possible to establish optimal dosages of ingredients.